Pengaruh Tingkat Konsentrasi Terhadap Hasil Belajar - Acep Fatchuroji; Sahriah Yunus; Misbahuddin Jamal; Grace Somelok; Riska Yulianti; Maria Sihombing (Departement of Mathematics Education, 2023)
This study aims to investigate the effect of concentration level on learning outcomes. The method used in this research is literature study, where data is obtained from literature sources related to the research topic. Data analysis is done using qualitative and quantitative approaches. The results show that the level of concentration significantly affects learning outcomes. The higher the level of concentration, the better the learning outcomes achieved. Other factors such as learning environment, motivation, and quality of teaching materials also influence learning outcomes. This research is important to provide understanding about factors that influence learning outcomes, especially the concentration factor. The results of this study can be a reference for teachers and students in optimizing the teaching and learning process. In conclusion, this research shows that the level of concentration plays an important role in achieving optimal learning outcomes.